Video Blog to Boost Young Learners' Speaking Skill - Raden Roro Ajeng Herdani Kusumaningrum; Nur Rifai Akhsan (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2023)
This research was conducted based on the problems that occur in seventh-grade students who have problems in speaking ability and in the method and media used in teaching English. This study aims to determine how effective video blog media is to teach speaking skills. This True-Experimental research was conducted at MTs Muhammadiyah Karangkajen Yogyakarta. The research design consisted of pre-test and post-test design. This study used a simple random sampling technique. The samples consist of 30 students in the experimental class and 30 students in the control class. In the data collection process, a test has been applied. This test has been validated by an expert in the English Education Study Program. After the test has been validated, the research was comducted a pre-test, four treatments, and post-test. Then the data was analyzed using Paired Samples Test with the SPSS 25.0 program. The result showed that the t-count value is 2.023 while the t-table resulted from df (29) and the two-tailed level of significance (0.05) is 1.699. This showed that the use of video blogs in teaching students' speaking skills has proven to be effective. As a result, it can be proven that the use of video blog media is more effective for teaching speaking skills than the use of text books and Power Point media.